A Thealogy of Radical Immanence: Goddess and the Posthuman. (September 2019) - Mantin, Ruth
In this article I offer possibilities for conversations between a feminist, post-realist thealogy and an exploration of the posthuman as presented by Rosi Braidotti. Braidotti draws on the influence of Baruch Spinoza to argue for an awareness of the 'radical immanence' which allows a challenge to the hierarchically dualistic assumptions of an anthropocentric paradigm. I maintain that the role of 'Goddess-talk' can contribute to this exploration with its figurations of a transgressive sacrality which can embrace ambiguity and plurality and which is immanent in a connection and interdependence with all forms of life. Such a thealogy can have points of contact with Braidotti's call for an interrogation of what is meant by 'being human', a consideration of the implications of a 'post-anthropocentric' world and a challenge to the ways in which a global capitalist economy is undertaking the commodification of life itself.